2007
DOI: 10.1007/s10832-007-9023-8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and electrical properties of multicomponent varistor ceramics with PbO–ZnO–B2O3 glass addition

Abstract: Zinc oxide based ceramics are widely used materials in varistors because of their excellent nonlinearity. Traditionally these ceramics are sintered at high temperatures (about 1,100-1,300°C). In this work a novel zinc oxide-based material with a low sintering temperature (900-1,000°C) was investigated. This material can be used in varistors consisting of several ceramic layers with embedded silver/palladium thick-film electrodes. This paper explains the research procedure employed with this novel varistor mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The erbium ions are situated between the layers. Moreover, the application of high pressure or high temperature can cause layers rebuilding from the non-cyclic 4 ] tetrahedral units (900-1100 cm − 1 ) [12][13][14][15]. The antisymmetric stretching mode causes that bands are centered at about 1050 cm − 1 , whereas the symmetric stretching frequency is located in the 850-900 cm − 1 region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The erbium ions are situated between the layers. Moreover, the application of high pressure or high temperature can cause layers rebuilding from the non-cyclic 4 ] tetrahedral units (900-1100 cm − 1 ) [12][13][14][15]. The antisymmetric stretching mode causes that bands are centered at about 1050 cm − 1 , whereas the symmetric stretching frequency is located in the 850-900 cm − 1 region.…”
Section: Resultsmentioning
confidence: 99%
“…The Zn-O distances in the [Zn 4 O] polyhedra are divided into two sets: a set of three shorter distances ranging from 1.83 to 1.91 Å and one with a longer interatomic distances (4.27 Å) than the sum of the van de Waals radii. Accordingly, the formation of three-coordination oxygens was necessary to compensate shortage of oxygens from zinc atoms.…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sintering with low‐melting point glass is the most effective and economical method for realizing high density of sintered ceramics at relatively low sintering temperatures . It has reported that the fabrication of MLVs with glass additives can evidently lower the sintering temperature, but at the same time, it will have some side effects on its nonlinear coefficient and voltage gradient as excessive dopant added . Consequently, there is a need to develop low‐temperature sintering MLVs with good nonlinear characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures below 1000°C would also enable the use of cheaper Ag contacts instead of the much more expensive Pd-or Ptcontaining ones [9][10][11][12][13][14][15]. Different approaches have been reported in order to prepare dense varistor ceramics with good I-U characteristics at temperatures below 1000°C, such as the use of fine starting powders with a high sinterability prepared by a polymerized complex method [16], a two-stage, low-temperature thermal processing [17,18], hot pressing [19] or the addition of low-melting glass frit [10,20]. They resulted in a high density of varistor ceramics; however, the breakdown voltages of the ceramics were still above 1000 V·mm -1 , which is much too high for most applications.…”
Section: Introductionmentioning
confidence: 99%